(untitled) (Sustainability in Debate, 2010)
At the beginning of the 21st century, the shortage of water is unquestionable constituting a threat to humanity and the biosphere. This situation is experienced in arid, Semi-arid and Mediterranean regions. The management of aquatic resources and the availability of water is a complex issue and of a huge strategic importance for sustainable development. The main objective of this paper is to present and discuss strategies for water management in the Mediterranean and Semi-arid regions through a literature review. As a conclusion, the semi-arid regions, due to its specific characteristics, will suffer more with water scarcity. Regarding the Mediterranean, all scenarios of future developments foresee a decline in rainfall, a trend which will bring serious impacts on society and environment. Hence, Mediterranean regions should focus in implementing simple techniques and lowcost used in semiarid regions, many of which currently abandoned but with centuries-old traditions in the history of the Mediterranean.